2018
DOI: 10.1016/j.bpj.2017.11.3463
|View full text |Cite
|
Sign up to set email alerts
|

Functional Charaterization of Zebrafish Transient Receptor Potential Melastatin 2

Abstract: Transient Receptor Potential Canonical 3 (TRPC3) channels have been demonstrated to underlie a slow excitatory postsynaptic current (sEPSC) that is coupled to the activation of type-1 metabotropic glutamate receptor (mGluR1) by glutamate release at the parallel fiber -Purkinje cell synapses of the cerebellum. On the other hand, Purkinje neurons receive extensive inhibitory synaptic inputs from interneurons located in the molecular layer of cerebellar cortex and GABA B receptors (GABA B Rs) are expressed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition to sensing Ca 2+ and ADPR, hs TRPM2 has been shown to sense body temperature to limit the fever response (11, 12). By contrast, dr TRPM2 lacks intersubunit interactions (28) and does not respond to heat or pH (36). We speculate that higher temperature, in the form of enhanced thermal motion, may overcome the intersubunit interactions in hs TRPM2 to modulate gating.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sensing Ca 2+ and ADPR, hs TRPM2 has been shown to sense body temperature to limit the fever response (11, 12). By contrast, dr TRPM2 lacks intersubunit interactions (28) and does not respond to heat or pH (36). We speculate that higher temperature, in the form of enhanced thermal motion, may overcome the intersubunit interactions in hs TRPM2 to modulate gating.…”
Section: Discussionmentioning
confidence: 99%
“…Human TRPM2 ( hs TRPM2) has several functional properties different from those of dr TRPM2 and invertebrate TRPM2, including temperature sensitivity and desensitization rate (Nam Tran et al, 2018; Iordanov et al, 2019). A recent publication suggested that hs TRPM2 does not bind ADPR in the MHR1/2 domain and that its activation is rather driven by ADPR binding in the NUDT9-H domain (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%